Principles of Coding and Reimbursement for Surgeons - Savarise, Mark.; Senkowski, Christopher; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text provides the in-depth understanding of the mechanisms that guide coding and reimbursement. The text is meant to be useful to surgeons in practice, both in general surgery and in surgical subspecialties; practice management teams of surgical practices and to resident physicians in surgery. Part 1 of the text addresses the CPT coding process, the relative valuation system (RVU), the ICD-9 and ICD-10 systems of classification, Medicare Part B payment rules for physicians, the DRG system and Medicare Part A payment for hospitals, alternative payment models, and the myriad of quality measures of importance to surgeons. Part 2 of the text addresses specific coding in areas where surgeons historically have had the most difficulty. This is not meant to substitute for the available texts, software or courses on coding, but to provide the historical background and rationale for the specific coding rules. Principles of Coding and Reimbursement for Surgeons will be of great value to general surgeons and surgical subspecialists in private practice, academic institutions, and employed positions. It will provide direction to management teams from practice and institutional levels. It is also of use to surgical trainees and to researchers in health policy issues.
Section I: History -- Section II: ICD Coding -- ICD-9 Coding -- ICD-10 Coding -- Section III: CPT -- The CPT Process and Panel -- CPT Application -- Section IV: The RUC -- Harvard Study and the Evolution of the RVU -- History of the RUC -- RVU Valuation Process -- How RVU have been Used for Physician Benchmarking -- Section V: Reimbursement -- CMS and the SGR -- Copays, Deductibles, Out of Pocket -- Billing and Collections -- Section VI: APC, DRGs and Hospital Reimbursement -- Medicare Part A -- DRG-Based Payment, CCs and MCCs and APCs -- How ASCs are Reimbursed Differently -- Durable Medical Equipment -- Section VII: Alternative Payment Schemes -- Bundled Payment Models -- Accountable Care Organizations -- Pay for Performance -- Section VIII: Quality Measures -- PQRS, SCIP and Other Existing Measures -- Pay for Performance -- Section IX: Specific Coding Issues -- Evaluation and Management -- Skin and Soft Tissue Procedures -- Breast -- Vascular -- GI -- Laparoscopy -- Bariatric -- Colon and Rectal -- Abdominal Wall -- Oncology -- Transplant -- Trauma and Critical Care -- Endoscopy.
Keywords: Medicine; Surgery; Medicine & Public Health; General Surgery